2020
DOI: 10.1371/journal.pone.0241810
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and health: The effects of the built environment on chronic disease risk factors among women in Tanzania

Abstract: Sub-Saharan Africa is experiencing rapid urban growth. Cities enable greater access to health services and improved water and sanitation infrastructure, leading to some improvements in health. However, urban settings may also be associated with more sedentary, stressful lifestyles and consumption of less nutritious food. C-reactive protein (CRP) is a measure of chronic inflammation predictive of cardiovascular disease, and high body mass index (BMI), a ratio of weight to height, indicates overweight or obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…However, rural-urban has no significant relationship with body weight in the multivariate analysis. A study conducted in Tanzania reported a similar finding ( 54 ).…”
Section: Discussionsupporting
confidence: 63%
“…However, rural-urban has no significant relationship with body weight in the multivariate analysis. A study conducted in Tanzania reported a similar finding ( 54 ).…”
Section: Discussionsupporting
confidence: 63%
“…We recommend that future studies (1) capture relevant distal and proximal factors potentially on the causal pathway (eg, quality of healthcare, exposure to air pollution) and (2) assess the extent of a dose–response relationship between NMR and increasing urban-nature of residence. 46 …”
Section: Discussionmentioning
confidence: 99%
“…(GHSL measures area, not volume, such as the vertical dimension of built-up areas or cities.) Elsewhere these data have been used to describe change in the extent or footprint of the urban environment (Balk et al, 2018) and as an indicator for urbanization of land area (Liu and Balk, 2020;Pinchoff et al, 2020;Gao and O'Neill, 2020). We use it independently to evaluate how much land in the LECZ is built-up.…”
Section: Built-up Densitymentioning
confidence: 99%